Cloud Based Multi-Level Security, Event Based Surveillance and Real-time access in Smart Homes using Zigbee: Real-time Access in Smart Homes Using Zigbee - Ali, Jawad; Zafar, Haseeb; Johar, Inamullah; Iqbal, Nasar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In recent years, smart home automation, real-time access to smart appliances, security & surveillance and inter-connected sensory node application are being the active topics for its considerable development. The work utilizes a smart home gateway that enables the bidirectional data streams to be converted between Wi-Fi protocol (IEEE 802.11b/g/n) and ZigBee protocol (IEEE 802.16.4, 6LoPAN). The paper describes the unified application of Infrared beam sensors & motion detectors (PIR BISS0001) and IP camera (ICamView IP-01b) in the smart home surveillance and reducing video data communication as well as needless storage of the video stream. The devices are remotely monitored using a server that can obtain a real-time connection upon the anomaly detection in the surveillance area. The ZigBee-WIFI gateway is solving the bottle-neck between the data rates of two different communication technologies, i.e., WIFI (VT6656) and ZigBee (JN5148). All the devices are remotely monitored by a centralized server that is making adequate decisions based on the data received from these IP based devices.